Case Report and Preliminary Exploration: Protection of Supraclavicular Nerve Branches during Internal Fixation of Clavicular Fractures through Preoperative Ultrasound Localization - Wang, Yulin; Huang, Jiapeng; Li, Jianjun; Zhou, Jinfeng; Zheng, Qiang; Chen, Zhixue; Wei, Penghui; Tang, Wenxi (Frontiers in Surgery, 2022)
Abstract Introduction: Protecting the supraclavicular nerve during internal fixation of clavicular fractures can reduce numbness in its innervation area after surgery. Previous methods for supraclavicular nerve protection are empirical, time-consuming, and approximate. In this report, we verified the feasibility of using ultrasound for percutaneous localization of the terminal branches of the supraclavicular nerve, and the feasibility of an ultrasound-guided skin flap reserve technique for nerve protection. Case Presentations: A high-frequency linear array probe was used in three cases to trace out the supraclavicular nerve from its origin at the superficial cervical plexus to the surface of the clavicle. In the first case, the feasibility of percutaneous ultrasound localization of the terminal branches of the supraclavicular nerve was determined by performing an ultrasound-guided nerve block. In the second case, the feasibility of this method was determined by directly isolating this nerve under direct vision. In the third case, after the ultrasound localization, the nerves were protected by intraoperative skin retention. In the first case, skin anesthesia of the innervation area of the intermediate branch of the supraclavicular nerve was achieved. In the second case, the part of the nerve that crosses the surface of the clavicle was quickly found and successfully protected, and no obvious abnormal skin sensations were noted after the operation. In the third case, there was no abnormal sensation in most of the associated skin except for the innervation area of the lateral branch of the supraclavicular nerve. Conclusions: The medial and intermediate branches of the supraclavicular nerve could be located over the skin by ultrasound, and this could be helpful in quickly isolating these nerves intraoperatively. Retaining the corresponding skin can protect the function of these nerve branches and effectively reduce the area of skin numbness after surgery.